The role of peer facilitator in enhancing english language proficiency in a simulated environment - Nur Salina, Ismail; Engku Suhaimi, Engku Atek; Mahani, Mohamad (Canadian Center of Science and Education, 2015)
For many learners, language class can be anxiety-provoking than other courses. Mostly, university students are seen to have language anxiety especially in their second language learning. They tend to be nervous when using English language in the formal situation like in classroom. English Outdoor Programme (EOP) in 2011 as part of informal setting was carried out by Universiti Sultan Zainal Abidin (UniSZA) in an effort to improve the standard of English of its students. The study aims to explore the role of peer facilitators in assisting the students learning English during the EOP from the view of participants and the peer facilitators themselves. This research applies mixed method approach using questionnaire and interview with both participants and peers involved in this programme. Data obtained from the questionnaire was analysed using SPSS and data from interview was analysed using thematic coding to answer the research objectives given. A significant finding is the positive role the peer facilitators had in the participants’ language learning process; not only for the participants but also the peer facilitators themselves.